Basketball Player Assumes the Risk of Injury: Editor: Thomas H. Sawyer. Issue 4 (4th May 2018) - Sawyer, Tonya L.
Abstract : The plaintiff allegedly was injured during a high school basketball game when he was kicked in the leg by another student. The court dismissed the claim on the grounds that the plaintiff had assumed the risk of injury when playing interscholastic basketball.